(3GddhGeY GdEdgjIs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s ((3eMeO WGgQ GdSeGhjs)
(3ChdgG (B:s
(3ChdgG(B: (3JSHjMGJ dLdGd eHOY fWb HBjGJ hLhH hLhOg ghjGJ GdCTjGA (B... (3GddhGeY GdChd aj eHGMK GdfXQ , hajg CHMGKs
(3BNQgG (B:s
(3BNQgG(B: (3hceG bGd SjOj Rjf GdYGHOjf Ydj Hf GdMSjf(B: (3jG QH Ef YUjJc abO CWYJc aj CMH GdCTjGA Edjc hgh GdJhMjO, hEf de CWYc ade CYUc aj CHZV GdCTjGA Edjc hgh GdTQc hGdBf adfbWY GdcdGe MGeOjf Gddg Ydi BdGFgs
(3efShN Yf fSNI MSfI GdNW cKjQI GdSbWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 282s
(3GdPQjYI, L (B18: 231s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds